2018
DOI: 10.1038/s41598-018-30387-9
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of genetic markers of recent human evolution in educational and cognitive traits

Abstract: Higher cognitive functions are regarded as one of the main distinctive traits of humans. Evidence for the cognitive evolution of human beings is mainly based on fossil records of an expanding cranium and an increasing complexity of material culture artefacts. However, the molecular genetic factors involved in the evolution are still relatively unexplored. Here, we investigated whether genomic regions that underwent positive selection in humans after divergence from Neanderthals are enriched for genetic associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…We used the data available from a multi-trait analysis of GWAS 61 , which, in our case, represents a joint polygenic score focused on a GWAS of cognitive performance and complemented by information from a GWAS on educational attainment, a GWAS on the highest-level math class completed, and a GWAS on self-reported math ability (data called MTAG_CP by the consortium). This joint analysis is ideal because pairwise genetic correlations of these traits were high 22 .…”
Section: Methodsmentioning
confidence: 99%
“…We used the data available from a multi-trait analysis of GWAS 61 , which, in our case, represents a joint polygenic score focused on a GWAS of cognitive performance and complemented by information from a GWAS on educational attainment, a GWAS on the highest-level math class completed, and a GWAS on self-reported math ability (data called MTAG_CP by the consortium). This joint analysis is ideal because pairwise genetic correlations of these traits were high 22 .…”
Section: Methodsmentioning
confidence: 99%
“…5 Both of these VNTRs were studied because they were found in close proximity to a genome-wide association study signal for the associated disease. The high incidence of neurological disease in humans is partly attributed to rapid changes in genes involved in brain function, [6][7][8] and tandem repeats are proposed to contribute to these human-specific traits. 9 To better understand the role that tandem repeats could play in human-specific brain health and disease, we took a genome-wide approach, looking for VNTRs that expanded only in humans and exhibited far greater variability in a neurological disease population, as compared to the reference genome.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the human brain plays a crucial role in developing improved cognitive functioning and has led to distinct patterns of behavior in humans compared to their primate relatives (Heyes 2012; Srinivasan et al 2018). During the course of evolution, humans have developed complex language (d’Errico et al 2003), executive functioning and abstract thinking (Barkley 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the genomic regions which are advantageous for the acquisition of important human traits such as language, complex cognitive skills and other favorable brain functions including behavioral flexibility also predispose to schizophrenia are also (Srinivasan et al 2016). Enrichment of recent evolutionary markers in the vicinity of schizophrenia (Xu et al 2015; Srinivasan et al 2016) and cognition (Srinivasan et al 2018) associated loci, suggest their involvement and importance for both these traits. Human accelerated regions (HARs) are one such class of genetic markers of recent evolution in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation